Synthesis of Sodium-Lead Apatite Structure with the Excess and the Lack of Sodium - Abdul Jabar, Mohammed A. B. (Iraqi Journal of Science, 2023)
X-ray phase analysis was used to analyse the composition of Pb8Na(2±x)(PO4)6 (lead-sodium apatite structure) with different X values (X values refer to changes in the excess or lack of sodium (2±X) in the apatite structure): -0.15, -0.10, -0.05, 0.00, +0.05, +0.10, and +0.15. The ceramic method (solid-state reaction) was used to synthesize all samples at a temperature of 800 °C. Many programs, such as match software (v.3), PDF-4 database (ICCD), and database PDF-4 (ASTM), were used to study the single phases. The least-squares method was used to calculate the unit cell parameters. Results have shown that the following compositions: Pb8Na2(PO4)6, Pb8Na1.95(PO4)6, Pb8Na1.90(PO4)6, and Pb8Na1.85(PO4)6 contain only the pure phase of lead sodium apatite structure. On the other hand, the compositions of Pb8Na2.05(PO4)6, Pb8Na2.10(PO4)6, and Pb8Na2.15(PO4)6 showed other phases besides the phases of lead sodium apatite structure.